A Community of Practice to increase education and collaboration in dementia and ageing research and care: The Liverpool Dementia & Ageing Research Forum - Clarissa Giebel; Hilary Tetlow; Thomas Faulkner; Ruth Eley (Health Expectations, 2023)
Abstract Background Too often, dementia research is conducted in research silos without thorough integration and the involvement of people with lived experiences, care professionals and the Third Sector. Research can also get lost in academic publications, without reaching those benefiting most from the evidence. The aim of this methods and evaluation paper was to outline the aims, components and evaluation of the public‐facing and ‐engaging Liverpool Dementia & Ageing Research Forum, to provide a blueprint for setting up similar communities of practice. Methods The Forum was set up in 2019 with the aim to (a) connect different stakeholders in dementia and ageing and co‐produce research and to (b) inform and educate. This paper provides an account of the Forum model and evaluates the following key elements: (1) engagement; (2) experiences of the Forum and its impact (via an online evaluation survey and three reflections). All Forum members and attendees were asked to complete a brief evaluation survey about their experiences from October to November 2022. Three regular Forum attendees provided a case study about their involvement and its impact. Findings The Forum has reached out to diverse stakeholders and the general public, generating growing interest and engagement since its initiation. Forty‐four members and attendees completed the survey. Most attendees completing the evaluation survey have so far engaged in between 5 and 20 activities (47.8%), and 91% felt the aims of the Forum have been met. Engaging in the Forum has produced various benefits for attendees, including increased research capacity and knowledge, as well as improved connectivity with other stakeholders. Eleven percent of respondents, 39% of lived experts, stated they experienced improved access to postdiagnostic care. Conclusions This is the first reported multistakeholder Community of Practice (CoP) on dementia and ageing. We make key recommendations for setting up and running similar dementia CoP, as they provide a noninterventional format for raising awareness, capacity and access to dementia care. Patient and Public Involvement This paper reports on the involvement and engagement of people with dementia, unpaid carers, health and social care providers and Third Sector organisations in a CoP.